Implementation of Nearpod on the Material of Healthy and Balanced Diet at Physical Education Classes of Junior High School (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The COVID-19 pandemic requires teachers to use technology in learning. The selection of technology as a learning support must be interesting and interactive, therefore, the students do not get bored in understanding the lesson. The purpose of this study was to compile materials for a healthy, nutritious and balanced diet on Nearpod. This study also examines the effectiveness of using Nearpod and examines the relationship between knowledge and diet. The research approaches used are the method of development, experimentation and correlation. The instruments used are material validator questionnaires, media, physical education teachers and students, interviews, observations, knowledge tests and documentation. The population and sample in this study were 7th grade of Junior High School students in Baki, Sukoharjo Regency which is divided into a small-scale trial of 30 students, 15 students in the control class and 15 students in the experimental class. While, in a large-scale trial of 90 students, 45 students in the control class and 45 students in the experimental class. Quantitative data analysis using SPSS 16 which includes validity, homogeneity, reliability, effectiveness and correlation tests. The assessment results of the preparation in the material for a healthy, nutritious and balanced diet obtained material validation for 96% of the